Impact of using lightweight eco-bricks as enclosures for individual houses of one story on zones of high seismicity - Domínguez, David; Muñoz, Pedro; Muñoz, Luis (Materiales de Construcción, 2018)
Fired clay bricks are widely developed by focusing on the use of several wastes with the aim of obtaining lightweight materials. Despite research having provided positives experiences, most of these showed an important reduction of compression strength. This issue must be highlighted in particular, when seismic areas are considered. However, despite compression strength decreases in some cases the energy that can be absorbed by the brick might be increased. Hence, this paper tests and shows physical and mechanical properties of newly fired clays made by adding different percentages of sawdust. Results are used for calculating the response of an individual one-story house to medium intensity earthquakes. It is concluded that the use of bricks, with up to 5% sawdust added, is an ecological way for recycling these agro-wastes, while its behaviour against earthquakes performs better than other solutions, such as common perforated bricks.
Impacto de la utilización de eco-ladrillos, como envolventes para viviendas unifamiliares de una planta, en zonas de alta sismicidad. Los ladrillos de arcilla cocida, fabricados con ciertos residuos, a fin de aligerarlos, es una alternativa ampliamente desarrollada. A pesar de que han dado resultados positivos, la mayor parte han mostrado una importante reducción de la resistencia mecánica. Este problema, es especialmente relevante cuando se considera su uso en zonas sísmicas. Sin embargo, a pesar de que la resistencia a la compresión disminuye, en algunos casos, la energía que puede absorber aumenta. De este modo, el artículo ensaya y muestra las propiedades físicas y mecánicas de la arcilla cocida, fabricada añadiendo serrín de madera. Los resultados obtenidos han servido para calcular la respuesta ante un sismo de intensidad media para un modelo de edificio de una planta. Se ha concluido que el uso de ladrillos fabricados con hasta el 5% de serrín, es una alternativa válida para el reciclaje de residuo agrícola y su comportamiento mecánico ante sismos es satisfactorio.
Keywords: Scopus; JCR